THE ROLE OF COMPETITIVE ADVANTAGE TO ENHANCE MARKETING PERFORMANCE: A STUDY ON INDONESIAN MSME BUSINESS COMMUNITY - Dorojatun Prihandono; Angga Pandu Wijaya; Aufaa Afiffah Ainii (Jurnal Bisnis Manajemen, 2021)
The rapid development of global business requires MSMEs to understand what the market needs. The research deals with the impact of competitive advantage as a pertinent variable in enhancing marketing performance in Indonesian MSMEs businesses. In this study, continuous competitive advantage is a focal idea to keep up with today’s disruptive market in the digital era. This study examines how market orientation and entrepreneurial orientation influence marketing performance through competitive advantage in MSMEs businesses in Indonesia. The study uses path analysis and data collection obtained by using a sample from the MSME business community. The results show that market orientation and entrepreneurial orientation have a positive and significant effect on marketing performance, and competitive advantage can mediate it. For MSME, it is hoped that it can increase response to competitors' actions, open-mindedness, be proactive in responding to market opportunities, and differentiation strategies.